Effects of anesthetics pentobarbital sodium and chloral hydrate on urine proteome - Mindi Zhao (PeerJ, 2015)
Urine can be a better source than blood for biomarker discovery since it accumulates many changes. The urine proteome is susceptible to many factors, including anesthesia. Pentobarbital sodium and chloral hydrate are commonly used anesthetics in animal experiments. This study demonstrated the effects of these two anesthetics on the rat urine proteome using liquid chromatography–tandem mass spectrometry (LC-MS/MS). With anesthesia, the urinary protein-to-creatinine ratio of all rats increased twofold. The relative abundance of 22 and 23 urinary proteins were changed with pentobarbital sodium or chloral hydrate anesthesia, respectively, as determined by label-free quantification. Among these changed proteins, fifteen had been considered as candidate biomarkers such as uromodulin, and sixteen had been considered stable in healthy human urine, which are more likely to be considered as potential biomarkers when changed, such as transferrin. The pattern of changed urinary proteins provides clues to the discovery of urinary proteins regulatory mechanisms. When determining a candidate biomarker, anesthetic-related effects can be excluded from future biomarker discovery studies. Since anesthetics take effects via nervous system, this study is the first to provide clues that the protein handling function of the kidney may possibly be regulated by the nervous system.